Effect of Pulmonary Rehabilitation on Inspiratory Capacity During 6-min Walk Test in Patients With COPD: A PROSPECTIVE CONTROLLED STUDY. Issue 4 (July 2018) - Spielmanns, Marc; Boeselt, Tobias; Nell, Christoph; Eckhoff, Jenny; Koczulla, Rembert Andreas; Magnet, Fridericke Sophie; Storre, Jan Hendrik; Windisch, Wolfram; Baum, Klaus
Abstract : Purpose: Purpose of this study was to analyze the impact of a pulmonary rehabilitation (PR) program on the measured inspiratory capacity (IC) in patients with chronic obstructive pulmonary disease (COPD) while performing a 6-min walk test (6MWT). Methods: Before and after PR, IC was measured by spirometry both at the beginning and at the end of the 6MWT for 15 patients with COPD in the PR group (PRG) and compared with a similar calisthenics training group (CTG; n = 15). In addition, the COPD Assessment Test (CAT), St George's Respiratory Questionnaire (SGRQ), and other lung function tests were recorded and compared. Results: Both groups were not significantly different at baseline. Compared with the CTG, the PRG achieved a significant increase in the delta of IC measured during the 6MWT (0.5 ± 0.2 L [PRG] vs −0.2 + 0.2 L [CTG], P = .001). Significant differences were found for the 6MWT walking distance (PRG: 99 ± 36 m vs CTG: 5 ± 25 m, P = .001). No significant increase in dyspnea while performing the 6MWT was found in either group. The differences in the CAT score and the SGRQ Global score were significant only for the PRG in intragroup comparisons, whereas the intergroup comparison showed no significant differences. Except for residual volume, no significant changes in all parameters of the static lung function tests were observed in either group. Conclusion: Participation in a PR may lead to a significant and clinically relevant increase in IC and the walking distance. Additional research is necessary to define the effects of this increase in IC on exercise capacity. Abstract : Supplemental Digital Content is Available in the Text.This study investigated the effects of an outpatient pulmonary rehabilitation (PR) program on dynamic inspiratory capacity (IC) in patients with chronic obstructive pulmonary disease. In comparison with a calisthenics training group, improvement of IC was found only in the PR group.